Utang Piutang Dalam Al-Qur’an: Kajian Tematik QS. Al-Baqarah: 282-282 Tentang Nilai-Nilai Etis Transaksi - Eka Rosyida Agustina; Abdul Syukkur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
Debt transactions constitute an important aspect of muamalah with social and ethical implications. The Qur’an addresses this issue in QS. Al-Baqarah: 282–283, which regulates debt transactions in detail. However, existing studies tend to emphasize legal and procedural aspects, with limited attention to their ethical dimensions. This study aims to analyze the ethical values of debt transactions in the Qur’an using a thematic (maudhu’i) tafsir approach. It employs a qualitative library research method. The analysis is conducted through stages of thematic interpretation, including determining the theme, collecting related verses, analyzing the context of the verses (asbāb al-nuzūl and munāsabah), and examining the interpretations of mufasirs. The findings reveal that these verses highlight not only procedural aspects, such as documentation and witnesses, but also ethical principles, including justice, trustworthiness, responsibility, and protection of vulnerable parties. This study offers an ethical reading of debt transactions, which have been predominantly understood in legal terms, thereby emphasizing their foundation in social justice within the Qur’anic framework.